Analisa Iklan Rokok Jarum 76 versi Jin Pingin Ganteng dalam Seni Ta ta Busana Jawa (Solo) - Jaelani, Muhammad Reza (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2014)
In Ads DJarum 76 jin wanted a handsome version of cultural approaches to advertise their products . By usingand utilizing the cultural approach is closely related to Indonesian society that is multicultural and very condensedcultural elements in their daily lives . Indonesia consists of 34 provinces and each province has its ownlanguage and a different culture . Therefore culture is very attached to the people of Indonesia . By using this Javanesecultural approach manufacturers expect their products acceptable in the midst of the people of Indonesiaare heterogeneous .In this study the authors chose the title â Semiotics Analysis Ads Djarum 76 Version Jin Pingin Gant in dressmakingArt Java (Solo ) . â Author will analyze Cigarette Ads Djarum 76 versions Jin wants Handsome Art dressmakingin Java (Solo ) by using semiotic analysis Roland Barthes . General Semiotics is the study of meaning 2 stages,denotation and connotation to the myth in a message communication , and which will be used as an interpretationin a semiotic analysis is contained in the meaning of images , signs , symbols , colors and shapes in a communicationmessage delivered